Calculation and analysis of plasma impedance during closing process of laser‐triggered vacuum switch. (November 2022) - Lu, Gang; Liao, Minfu; Zhang, Ming; Sun, Yifan; Ou, Jian; Duan, Xiongying; Han, Xiaotao
Abstract: The plasma characteristics of laser‐triggered vacuum switch (LTVS) have significant effects on the output characteristics of a pulsed power system during closing process. The plasma impedance can link the microscopic properties of plasma and the macroscopic electrical parameters effectively. In this paper, the mathematic representations of plasma impedance are calculated theoretically with the equivalent circuit. External circuit inductance and resistance are calculated by means of ANSYS software and discharge time constant, respectively. Furthermore, the current and voltage experimental waveforms during closing process are analyzed by fitting piecewise linear functions in MATLAB. The plasma impedance can be calculated based on the above conditions. The calculation results show that the plasma resistance reduces with time exponentially, which is caused by an exponential increase in electron density during closing process. In addition, the plasma inductance shows an overall trend of decreasing over time, but there are fluctuations. Highlights: The plasma resistance reduces with time exponentially during LTVS closing process. During LTVS closing process, the plasma inductance shows an overall trend of decreasing over time. Operating voltage affects the plasma impedance during LTVS closing process.